A method and device for treating VOC waste gas
Through integrated VOC adsorption-catalytic degradation and exhaust CO2 reuse technology, VOC waste gas is photocatalyticly degraded and CO2 mixed with high magnesium-lithium salt lake brine for CO2 mineralization, which solves the problems of high energy consumption and CO2 accumulation in the existing technology, and achieves efficient degradation of VOC waste gas and low CO2 emissions.
Patent Information
- Application Number
- CN202210935541.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-05
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-08-05
AI Technical Summary
The existing VOC catalytic degradation technology requires high energy consumption, and the accumulation of CO2 generated has an impact on the environment, and lacks integrated technologies for low-temperature catalytic degradation and CO2 reuse.
The integrated VOC adsorption-catalytic degradation and exhaust CO2 reuse technology are used to degrade VOC exhaust gas by photocatalytic degradation, and the CO2 trapping agent is used to capture and desorb concentrated CO2, and finally the enriched CO2 is mixed with the high magnesium-lithium-specific salt lake brine to allow magnesium to mineralize CO2.
The effective degradation of low-concentration VOC exhaust gas and low emission of exhaust CO2 are achieved, process operation is simplified, energy consumption is reduced, and secondary pollution is avoided through CO2 reuse.
Smart Images

Figure CN115318097B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of environmental catalysis, and more specifically, relates to a method and a device for treating VOC waste gas. Background Art
[0002] Air pollution purification has become one of the focuses of public attention, especially the purification of VOC (volatile organic compounds) in the air. VOCs come from a wide range of sources, including industrial processes, transportation, building materials, and home cooking. Due to their volatility, diffusion, and high toxicity, VOCs pose a great potential threat to the ecological environment and human health.
[0003] At present, many VOC purification technologies have been developed, including physical means such as adsorption (such as activated carbon), pressure swing adsorption separation and purification (such as zeolite molecular sieve), liquid absorption (non-chemical absorption), condensation recovery, membrane separation, and thermal destruction (such as direct combustion, catalytic combustion), biodegradation, oxidation (such as thermal oxidation, catalytic oxidation), and low-temperature plasma technology. Chemical means. Among them, physical means are mainly based on the adsorption mechanism to only complete the transfer of pollutants, but have great limitations in completely eliminating polluting components. In addition, membrane separation methods have the disadvantages of high cost, poor stability, and low flux, which limit the widespread application of this technology in industry. In contrast, catalytic oxidation technology completely removes low-concentration VOCs by catalytically converting VOCs into CO2 and H2O.
[0004] In the VOC catalytic degradation process, there are many studies based on low-temperature thermal catalysis. It is generally preferred to degrade VOC into CO2 and H2O at 200-350°C, thus avoiding the pollution of harmful substances such as dioxins produced by the high-temperature incineration process. However, this process still requires high energy consumption and requires strict control of reaction temperature, atmosphere and other conditions, and the operation is relatively complicated. In addition, the accumulation of CO2 produced from VOC degradation will also have an impact on the environment (such as the greenhouse effect). Therefore, it is urgent to develop a new type of integrated technology that can catalytically degrade low-concentration VOCs and eliminate CO2 at lower temperatures. Summary of the invention
[0005] The purpose of the present invention is to provide a method and device for treating VOC waste gas, which belongs to an integrated VOC adsorption-catalytic degradation and tail gas CO2 recycling technology. The present invention can photocatalytically degrade VOC waste gas at room temperature and realize the reuse of CO2 in the degradation product to avoid secondary pollution.
[0006] In a first aspect, the present invention provides a method for treating VOC waste gas, the method comprising:
[0007] 1) In the presence of adsorption-catalytic degradation materials, VOC waste gas is subjected to photocatalytic degradation reaction to obtain degradation products containing CO2 and water;
[0008] 2) in the presence of a CO2 capture agent, capturing CO2 in the degradation product, allowing the CO2 to be adsorbed on the CO2 capture agent, and then desorbing and concentrating the CO2 to obtain enriched CO2;
[0009] 3) Mixing the enriched CO2 with salt lake brine with a high magnesium-lithium ratio to mineralize the magnesium in the brine with CO2.
[0010] In a second aspect, the present invention provides a treatment device used in the VOC waste gas treatment method, the treatment device comprising a stage I adsorption-catalytic reaction device, a stage II CO2 capture device and a stage III CO2 application device connected in sequence, wherein the stage I adsorption-catalytic reaction device is used to enrich the VOC waste gas and photocatalytically degrade it into degradation products containing CO2 and H2O, the stage II CO2 capture device is used to capture, desorb and concentrate the CO2 in the degradation products to obtain enriched CO2, and the stage III CO2 application device is used to contact the enriched CO2 with high magnesium-lithium ratio salt lake brine to mineralize magnesium.
[0011] The method of the present invention achieves the goal of effective degradation of VOC waste gas (especially low-concentration VOC) and low emission of tail gas CO2 by integrating the three processes of adsorption-catalytic degradation of VOC, capture and enrichment of tail gas CO2, and reuse of enriched CO2. In a preferred embodiment, the method of the present invention can achieve efficient degradation of benzene in benzene-containing waste gas and zero emission of tail gas CO2.
[0012] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Exemplary embodiments of the present invention will be described in more detail with reference to the accompanying drawings.
[0014] Figure 1 This is a schematic structural diagram of a VOC waste gas treatment device used in one embodiment of the present invention.
[0015] Description of Reference Numerals
[0016] 1-VOC waste gas inlet; 2-primary dust removal component; 3-intermediate dehumidification component; 3a-gas flowmeter; 3b, 3c-valves; 4-closed light-shielding reaction chamber; 5-light-transmitting quartz; 5a-top lamp; 6-catalytic reactor; 7-light-transmitting quartz; 7a-bottom lamp; 8-II-level CO2 capture device; 9-dehumidification component; 10-CO2 adsorption component; 11-CO2 desorption fan; 12-gas flowmeter; 13-III-level CO2 application device; 14-reactor; 15-agitator; 16-exhaust gas outlet after purification; 17-filter, 18-liquid separation device, 19-liquid outlet. DETAILED DESCRIPTION
[0017] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0018] According to a first aspect of the present invention, the present invention provides a method for treating VOC waste gas, the method comprising:
[0019] 1) In the presence of adsorption-catalytic degradation materials, VOC waste gas is subjected to photocatalytic degradation reaction to obtain degradation products containing CO2 and water;
[0020] 2) in the presence of a CO2 capture agent, capturing CO2 in the degradation product, allowing the CO2 to be adsorbed on the CO2 capture agent, and then desorbing and concentrating the CO2 to obtain enriched CO2;
[0021] 3) Mixing the enriched CO2 with salt lake brine with a high magnesium-lithium ratio to mineralize the magnesium in the brine with CO2.
[0022] In the present invention, the VOC waste gas can be a flue gas mixture containing volatile organic compounds (VOC) and a small amount of dust and water vapor emitted from industrial production. The method of the present invention is suitable for treating low-concentration VOC waste gas, wherein the VOC concentration in the VOC waste gas is less than 150 mg·m -3 , preferably less than 120 mg·m -3 The VOC in the VOC waste gas may be at least one of benzene, toluene, ethylbenzene, xylene, chlorobenzene, styrene, formaldehyde and acetaldehyde, preferably at least one of benzene, toluene, ethylbenzene and xylene.
[0023] In the present invention, the adsorption-catalytic degradation material comprises a catalyst carrier and an active component. According to one embodiment, the catalyst carrier is a MOF adsorption material I, and the active component comprises TiO2 and a doping metal.
[0024] In the present invention, the MOF adsorbent material I is a MOF material with a high specific surface area and strong adsorption force for VOC, and can be specifically selected from at least one of MIL-101 (Cr), HKUST-1 and UIO66. The MOF adsorbent material I can be obtained by a commercial method or prepared by a method well known in the art. The active component is a doped metal-TiO2 composite material, wherein the doped metal can be selected from at least one of silver, copper, iron, cobalt, nickel and cerium.
[0025] Preferably, the MOF adsorption material I is MIL-101 (Cr), which can further improve the catalytic degradation efficiency of VOC.
[0026] According to a preferred embodiment, based on the total weight of the adsorption-catalytic degradation material, the content of the catalyst carrier is 92-99% by weight, and the content of the active component is 1-8% by weight; based on the total weight of the active component, the content of the doped metal in terms of its oxide is 1-6% by weight. In the present invention, the content of the active component in the degradation material is measured by fluorescence analysis.
[0027] In the present invention, the adsorption-catalytic degradation material can be obtained by first preparing the active component, and then subjecting the active component to a hydrothermal synthesis method with the MOF adsorption material I. Among them, the active component (doped metal-TiO2 composite material) can be prepared by methods well known in the art, for example, by sol-gel method, solvent thermal method, electrodeposition method, template-assisted method, spin coating method, dip coating method, chemical vapor deposition method, atomic layer deposition method, etc. It is preferred to prepare the doped metal-TiO2 composite material by sol-gel method, which not only has a simple preparation method, but also enables the composite material to obtain a larger specific surface area.
[0028] According to a specific embodiment, the adsorption-catalytic degradation material is prepared by a method comprising the following steps:
[0029] A) mixing tetrabutyl titanate, benzyl alcohol, ethanol and water and stirring the mixture at 0-5° C. to obtain a TiO2 sol;
[0030] B) adding a soluble salt of a doping metal to the TiO2 sol, stirring, and obtaining a precipitation mixed solution (a solid-liquid mixture with a precipitate);
[0031] C) centrifuging and filtering the precipitated mixed solution, and air-drying the solid obtained by filtration;
[0032] D) calcining the air-dried sample to obtain an active component (doped metal-TiO2 composite material);
[0033] E) mixing the MOF adsorbent material I, the active component and isopropanol, and performing ultrasonic dispersion to obtain a dispersion;
[0034] F) subjecting the dispersion to magnetic stirring, centrifugation, and filtering, and washing the solid (precipitate) obtained after filtering with isopropanol and standing to air-dry;
[0035] G) The air-dried sample is mixed with water and transferred to an autoclave and kept at 130-150° C. for 8-12 hours, then cooled and filtered to obtain the adsorption-catalytic degradation material.
[0036] In step A), the mass ratio of tetrabutyl titanate, benzyl alcohol, ethanol and water is preferably (3-5): (5-7): (48-51): 1. The stirring time may be 1-5 hours, for example, 1 hour, 2 hours, or 3 hours.
[0037] In step B), the soluble salt of the doped metal may be a nitrate of the doped metal or a hydrate of its nitrate, such as Cu(NO3)2·3H2O, Cu(NO3)2, Ce(NO3)3, etc. The stirring time may be 1-3 hours, such as 1 hour or 2 hours.
[0038] In step C), the centrifugal separation speed can be 300-500 rpm, and the centrifugal time can be 2-10 min, such as 3 min, 5 min, 8 min. The static air drying can be carried out at room temperature (20-30° C.), and the static air drying time can be 10-36 h, such as 12 h, 16 h, 24 h, 36 h.
[0039] In step D), the calcination temperature may be 300-400° C., such as 300° C., 350° C., or 400° C., and the calcination time may be 0.5-3 h, such as 1 h, 1.5 h, or 2 h.
[0040] In step E), the mass ratio of the MOF adsorbent material I, the active component and isopropanol can be 1:(1-1.2):(63-66). The ultrasonic dispersion time can be 20-60 min, such as 25 min, 30 min, 40 min.
[0041] In step F), the magnetic stirring time can be 5-10 hours, for example, 5 hours, 6 hours, 7 hours, 8 hours, and the magnetic stirring can be performed at room temperature. The number of washings can be multiple times, for example, 2 times, 3 times. The standing air drying can be performed at room temperature, and the standing air drying time is, for example, 6-10 hours, for example, 8 hours.
[0042] In step G), the air-dried sample is transferred to the autoclave for insulation for 10-12 hours.
[0043] According to the present invention, in step 1), the photocatalytic degradation reaction is carried out under certain reaction conditions, which include the relative humidity of the VOC waste gas, the reaction space velocity of the adsorption-catalytic degradation, and the visible light power density.
[0044] According to one embodiment, the reaction conditions of the photocatalytic oxidation degradation reaction include: the relative humidity of the VOC waste gas is 20-60%, for example, 20, 30%, 40%, 50%, 60%, and the reaction space velocity is 150-200h -1 (e.g. 150h -1 、180h -1 , 200h -1 ), the visible light source for adsorption-catalytic degradation is a lamp with a power of 20-30W, and the visible light power density is 0.05-0.1W / cm 2 , the irradiation time is 24-48h. In addition, the reaction temperature is preferably room temperature (20-30°C). In the present invention, relative humidity refers to the ratio of the absolute humidity in the air to the saturated absolute humidity at the same temperature and pressure. Preferably, in step 1), the relative humidity of the VOC waste gas is controlled to be 30-50%, which can further improve the catalytic degradation efficiency of the adsorption-catalytic degradation material.
[0045] In step 2), the CO2 capture agent is a MOF adsorbent material II or an organic amine-modified MOF adsorbent material II. The MOF adsorbent material II is a MOF material with a strong CO2 capture capability, specifically selected from at least one of Mg-MOF-74, ZIF-8 and MIL-53 (A1). The MOF adsorbent material I can be obtained by commercial methods or prepared by methods well known in the art.
[0046] In a specific embodiment, the MOF adsorption material II is Mg-MOF-74, which is prepared by the following method: first, in a reaction bottle, 4,4′-dihydroxy-3,3′-biphenyldicarboxylic acid, magnesium nitrate, ethanol and DMF are mixed in a mass ratio of 1:(2.5-3.5):(0.4-0.6):(0.4-0.6) and ultrasonically dispersed to form an emulsion; then, under the condition of sealing the reaction bottle, the emulsion is heated and stirred at 110-130°C for 20-30h to obtain a precipitate; then, the precipitate is filtered, and the obtained solid is washed with DMF for multiple times (for example, 3 times), and then immersed in methanol for multiple times (for example, 3 times), filtered to obtain a solid sample; finally, the solid sample is heated (for example, heated to 150-220°C) to remove the solvent to obtain Mg-MOF-74.
[0047] The organic amine modification can introduce amine groups into the MOF adsorbent material II to obtain an amine-functionalized MOF adsorbent material II. Preferably, the organic amine is selected from at least one of diethylamine, diethylenetriamine and tetraethylenepentamine.
[0048] Preferably, the CO2 capture agent is Mg-MOF-74 modified with organic amine.
[0049] In the present invention, the organic amine-modified MOF adsorbent material II can be prepared by referring to methods well known in the art, for example, by an impregnation method, a grafting method, or a direct synthesis method. Preferably, the organic amine-modified MOF adsorbent material II is synthesized by an impregnation method, which is not only simple in steps, but also can achieve high amine group loading.
[0050] In a preferred embodiment, the organic amine-modified MOF adsorbent material II is prepared by a method comprising the following steps:
[0051] Step I: Under an inert atmosphere (e.g., a nitrogen atmosphere), MOF adsorbent material II, an organic amine, and hexane are uniformly mixed in a mass ratio of (98-101):1:(9-11), and then allowed to stand for 3-6 hours (e.g., 3 hours, 4 hours, 5 hours) to obtain an aminated sample;
[0052] Step II: washing the aminated sample with hexane and drying to obtain the CO2 capture agent; preferably, the drying is vacuum drying at a drying temperature of 100-130° C. to remove the solvent in the pores.
[0053] According to the present invention, in step 2), the CO2 capture agent is used to capture CO2 at room temperature (25°C), and the CO2 capture agent has an adsorption capacity of 88-350 mg / g for CO2. The adsorption capacity refers to the adsorption capacity at room temperature and pressure (1 bar).
[0054] In step 2), the desorption temperature of the CO2 capture agent can be 100-135°C, preferably 120-130°C, and the desorption time is 8-10h.
[0055] According to the present invention, in step 3), by contacting the enriched CO2 with the salt lake brine with a high magnesium-lithium ratio, magnesium can be mineralized on the one hand to achieve the enrichment of lithium elements, and on the other hand, the secondary pollutant CO2 can be efficiently removed to achieve the secondary purification of tail gas. The present invention does not particularly limit the treated high magnesium-lithium ratio salt lake brine, which can be brine from various sources, such as the Yiliping Salt Lake brine in the Qaidam Basin of Qinghai, the Xitaijinaier Salt Lake brine, or simulated brine.
[0056] Step 3) comprises: combining CO2 mineralization with solvent extraction to continuously convert the enriched CO2 to Mg in the high magnesium-lithium ratio salt lake brine into precipitated MgCO3, preferably comprising the following process:
[0057] 3-1) in the presence of an extractant and a solvent, the enriched CO2 and the high magnesium-lithium ratio salt lake brine are mixed and stirred for reaction; wherein the extractant is selected from N, N-dioctyl-1-octylamine and / or triethylamine, and the solvent is selected from at least one of butanediol, pentanediol and isoamyl alcohol;
[0058] During the stirring reaction, MgCO3 precipitate and HCl are generated, and HCl reacts with the extractant to generate ammonium salt;
[0059] 3-2) The solid-liquid product containing the MgCO3 and ammonium salt obtained in step 3-1) is filtered to obtain a filter cake and a filtrate, the filter cake is washed and dried to obtain MgCO3, and the filtrate is allowed to stand and separated to obtain an organic phase and an aqueous phase, the organic phase mainly contains the extractant and the solvent, and the aqueous phase mainly contains lithium-containing brine. The volume ratio of the enriched CO2 to the high magnesium ratio salt lake brine can be (72-100):100.
[0060] In step 3-1), preferably, the volume ratio of the high magnesium-lithium ratio salt lake brine, the extractant and the solvent is (1-1.2):(0.8-1.2):1, and the stirring reaction time is 2-2.5h.
[0061] Preferably, the mass ratio of MgCl2 and LiCl in the high magnesium-lithium ratio salt lake brine is (25-30) : 1 in terms of Mg / Li.
[0062] In step 3-1), the temperature of the stirring reaction is preferably 18-25°C, such as 18-22°C. The temperature can be controlled by a water bath, and the stirring can be magnetic stirring.
[0063] In step 3-2), the filtrate may be allowed to stand for 0.5-1 h.
[0064] According to a second aspect of the present invention, the present invention provides a treatment device used in the VOC waste gas treatment method of the first aspect of the present invention, such as Figure 1As shown, the device includes: a stage I adsorption-catalytic reaction device, a stage II CO2 capture device 8 and a stage III CO2 application device 13 connected in sequence; wherein the stage I adsorption-catalytic reaction device is used to enrich the VOC waste gas and photocatalytically degrade it into degradation products containing CO2 and H2O, the stage II CO2 capture device 8 is used to capture, desorb and concentrate the CO2 in the degradation products to obtain enriched CO2, and the stage III CO2 application device 13 is used to contact the enriched CO2 with high magnesium-lithium ratio salt lake brine to mineralize magnesium.
[0065] According to a specific implementation mode, Figure 1 As shown, the I-stage adsorption-catalytic reaction device is provided with a VOC waste gas inlet 1, a primary dust removal component 2, an intermediate dehumidification component 3, and a closed light-shielding reaction chamber 4. Among them, the top of the closed light-shielding reaction chamber 4 is provided with a light-transmitting quartz 5 and a top lamp 5a, the bottom is provided with a light-transmitting quartz 7 and a bottom lamp 7a, and the middle is a catalytic reactor 6 containing the adsorption-catalytic degradation material. In addition, the 3-intermediate dehumidification component can be connected to the closed light-shielding reaction chamber 4 through a pipeline provided with a gas flowmeter 3a and valves 3b and 3c to control the flow rate and entry mode of the waste gas to be treated. The bottom of the I-stage adsorption-catalytic reaction device is connected to the top of the II-stage CO2 capture device 8 through a pipeline.
[0066] The interior of the II-level CO2 capture device 8 is provided with a dehumidification component 9, a CO2 adsorption component 10 and a CO2 desorption fan 11 from top to bottom, wherein the CO2 adsorption component 10 contains the CO2 capture agent and is provided with a heater outside thereof, through which a desorption temperature is provided for desorbing CO2. The bottom of the II-level CO2 capture device 8 can be connected to the top of the III-level CO2 application device 13 through a pipeline provided with a gas flowmeter 12.
[0067] The III-level CO2 application device 13 is provided with an outlet 16 for purified exhaust gas and a lithium purification component from high magnesium-lithium ratio brine, and the component is provided with a reactor 14, a filter 17, and a liquid separator 18 in sequence according to the material flow direction, and the reactor 14 is provided with an agitator 15. The III-level CO2 application device 13 is also provided with a liquid outlet 19, and the treated liquid (aqueous phase, organic phase) can flow out through the liquid outlet 19.
[0068] According to a specific embodiment, the processing method of the present invention is Figure 1 The processing device shown is implemented in the embodiment of the present invention, comprising:
[0069] 1) The VOC waste gas to be treated is sent into the I-stage adsorption-catalytic reaction device through the VOC waste gas inlet 1, and after the dust in the waste gas is removed by the primary dust removal component 2, it enters the intermediate dehumidification component 3 to remove the moisture, and the obtained reactant enters the closed light-shielding reaction chamber 4, and in the catalytic reactor 6, under the action of the adsorption-catalytic degradation material, the reactant is adsorbed and photocatalytically degraded to obtain a degradation product containing CO2 and water; during the reaction, with the assistance of transparent quartz 5 and 7, light source is provided by the top lamp tube 5a and the bottom lamp tube 7a.
[0070] 2) The degradation product enters the device from the bottom of the I-stage adsorption-catalytic reaction device through a pipeline and from the top of the II-stage CO2 capture device 8. After the water vapor is removed by the dehumidification component 9, the resulting gas is passed through the CO2 adsorption component 10 to achieve targeted capture of CO2. The captured CO2 is desorbed by the desorption fan 11 to obtain enriched CO2;
[0071] 3) The enriched CO2 enters the device from the bottom of the II-level CO2 capture device 8 through a pipeline and from the top of the III-level CO2 application device 13. During this period, its flow rate is controlled by a gas flowmeter 12. The enriched CO2 enters the reactor 14, and is mixed with the high magnesium-lithium ratio salt lake brine, solvent and extractant therein. The agitator 15 (such as a magnetic agitator) is stirred to produce a precipitate. The precipitate is filtered through a filter 17. The obtained filtrate enters a liquid separator 18 to extract and remove the organic phase containing the extractant to obtain an aqueous phase containing lithium brine. At the same time, the waste gas generated is discharged through the exhaust gas purification outlet 16, and the liquid is discharged through the liquid outlet 19.
[0072] Compared with the prior art, the processing method of the present invention has the following advantages:
[0073] (1) The integrated VOC adsorption-catalytic degradation and tail gas CO2 recycling method provided by the present invention realizes the integrated treatment of low-concentration VOC waste gas and CO2; compared with the traditional method of studying VOC degradation or CO2 capture separately, the method provided by the present invention is not only simple and fast, but also greatly reduces the process cost caused by multiple waste gas treatments;
[0074] (2) Compared with the existing method of catalytic degradation of VOCs by heat, it is preferred to use metal-doped TiO2 catalyst to implement the method of photocatalytic degradation of VOCs at room temperature, which not only simplifies the operation but also reduces the process energy consumption;
[0075] (3) The present invention preferably introduces microporous materials as catalyst carriers to enhance the carrier's adsorption performance for VOCs, which is beneficial to improving the adsorption capacity and degradation efficiency of the catalyst composite material for VOCs;
[0076] (4) The treatment device provided by the present invention can degrade harmful VOCs at one time at room temperature and effectively utilize the degraded exhaust gas CO2, thereby eliminating the threat posed by VOCs to the surrounding environment and human health.
[0077] The present invention will be further described below in conjunction with embodiments, but the scope of the present invention is not limited to these embodiments.
[0078] In the following examples, benzene-containing waste gas (mainly composed of benzene, water vapor and carbon black dust) is used as a low-concentration VOC model (benzene concentration is 100 mg·m -3 ).
[0079] MIL-101(Cr) was synthesized according to the literature method (DOI: 10.1126 / science.1116275): terephthalic acid (166 mg, 1 mmol), Cr(NO3)3.9H2O (400 mg, 1 mmol), hydrofluoric acid (0.2 mL, 1 mmol), and H2O (4.8 mL, 265 mmol) were subjected to a hydrothermal reaction at 220°C for 8 hours to form a green powder. The obtained green powder sample was further washed three times with 60°C ethanol to remove the unreacted and / or blocked terephthalic acid in the pores to obtain MIL-101(Cr).
[0080] The brine was simulated brine. MgCl2 and LiCl were dissolved in deionized water to form a mixed solution. The mass ratio of magnesium to lithium in the mixed solution was controlled to be 26:1. 2+ The initial concentration (C1) was 100 g / L.
[0081] Unless otherwise stated, Figure 1 The treatment device shown treats the waste gas containing benzene:
[0082] 1) The benzene-containing waste gas to be treated is sent to a first-stage adsorption-catalytic reaction device to remove dust and water vapor, and the resulting reactant enters a catalytic reactor and undergoes a photocatalytic degradation reaction under the action of an adsorption-catalytic degradation material to obtain a degradation product containing CO2 and water;
[0083] 2) The degradation product enters the II-stage CO2 capture device, and after removing the water vapor in the CO2 gas flow, the obtained gas is subjected to the targeted capture of CO2 by the CO2 capture agent, and the captured CO2 is concentrated by desorption to obtain enriched CO2;
[0084] 3) The enriched CO2 is introduced into the reaction bottle of the III-level CO2 application device, mixed with brine, solvent and extractant, and reacted at 18-22°C for 2.5 hours under stirring (the volume ratio of the enriched CO2 to the brine is 85:100). The obtained product is filtered, and the filter cake is washed with deionized water and anhydrous ethanol to obtain a washing phase. The filtrate is allowed to stand for 40 minutes and then separated to obtain an organic phase and an aqueous phase. The CO2 and benzene concentrations at the outlet 16 after the exhaust gas purification are detected by gas chromatography, and the Mg content in the washing phase and the aqueous phase is tested by EDTA analysis. 2+ The concentrations are C2 (g / L) and C3 (g / L), combined with Mg 2+ The initial concentration C1 (g / L) was used to obtain the magnesium conversion rate: magnesium conversion rate (%) = [(C1-C2-C3) / C1]×100%.
[0085] Example 1
[0086] The adsorption-catalytic degradation material of the I-stage adsorption-catalytic reaction device is Cu-TiO2 / MIL-101(Cr);
[0087] The CO2 capture agent of the Level II CO2 capture device is amine-functionalized Mg-MOF-74.
[0088] 1. Level I adsorption-catalytic reaction device
[0089] (1) Preparation of adsorption-catalytic degradation materials
[0090] The catalytic degradation material comprises 92.1 wt% of a carrier and 7.9 wt% of an active component, and the preparation method is as follows:
[0091] a) mixing tetrabutyl titanate with benzyl alcohol, ethanol and water (mass ratio of the four is 4:6:50:1), and stirring the resulting mixture at 0° C. for 1 h to mix uniformly to obtain a TiO2 sol;
[0092] b) adding Cu(NO3)2·3H2O to the TiO2 sol and stirring for 1 h to obtain a precipitated mixed solution;
[0093] c) centrifuging the precipitated mixture at 500 rpm for 5 min, filtering, and air-drying the resulting solid at room temperature for 24 h;
[0094] d) calcining the air-dried sample at 300°C for 1 h to obtain 2 wt% Cu-TiO2;
[0095] e) MIL-101(Cr), 2wt% Cu-TiO2 and isopropanol were mixed (the weight ratio of the three was 1:1:65), and the mixed sample was ultrasonically dispersed for 30 minutes, and then magnetically stirred for 8 hours to obtain a reaction sample;
[0096] f) The reaction sample was centrifuged and filtered in sequence, and the obtained solid was washed three times with isopropanol and air-dried at room temperature for 48 hours;
[0097] g) The air-dried sample was mixed with ultrapure water at a weight ratio of 1:50 and transferred to a 150°C autoclave for 10 h, cooled to room temperature, filtered and dried at 120°C for 24 h to obtain 2 wt% Cu-TiO2 / MIL-101(Cr).
[0098] (2) Reaction conditions
[0099] In the photocatalytic oxidation degradation reaction, the relative humidity of the benzene-containing waste gas to be reacted is 40%, and the reaction space velocity is 150h -1 The visible light source is a 20W lamp tube, and the visible light power density is 0.05W·cm 2 The irradiation time was 24 h and the reaction was carried out at room temperature.
[0100] 2. Level II CO2 capture device
[0101] (1) Preparation of amine-functionalized Mg-MOF-74
[0102] a) mixing 4,4′-dihydroxy-3,3′-biphenyldicarboxylic acid, magnesium nitrate, ethanol and DMF in a flask (the mass ratio of the four reagents is 1:3:0.5:0.5) and dispersing to form an emulsion;
[0103] b) sealing the flask and heating and stirring at 120° C. for 24 h to obtain a mixture containing a precipitate;
[0104] The mixture was filtered, and the obtained solid was washed three times with fresh DMF reagent, then soaked in methanol three times, and filtered to obtain a solid sample;
[0105] c) heating the solid sample at 200° C. to remove the solvent in the sample to obtain Mg-MOF-74;
[0106] d) Under N2 atmosphere, Mg-MOF-74, ethylenediamine and hexane were mixed evenly in a flask (the mass ratio of the three was 100:1:10), sealed and allowed to stand for 4 hours to obtain an aminated sample;
[0107] e) The aminated sample was washed three times with hexane and heated at 100° C. under vacuum to remove the solvent in the pores for 4 h to obtain aminated Mg-MOF-74, i.e., a CO2 capture agent.
[0108] (2) Reaction conditions
[0109] The outer wall heater of the II-stage CO2 capturer is controlled so that the desorption temperature is 130°C, the desorption time is 8h, the adsorption amount of CO2 by the CO2 capture agent is 295mg / g, and the adsorption is carried out at room temperature.
[0110] 3. Class III CO2 application device
[0111] CO2 mineralization is combined with solvent extraction so that the enriched CO2 can continuously convert the Mg in the brine into precipitated MgCO3, so as to achieve effective utilization of tail gas CO2. The solvent is butanediol, the extractant is N, N-dioctyl-1-octylamine, and the volume ratio of brine, extractant and solvent is 1:1:1;
[0112] In addition, the benzene-containing exhaust gas at the air inlet was controlled to be 100 mL / min, the loading amount of the adsorption-catalytic degradation material was 35 mL, and the size of the catalytic reactor was 4 cm×5 cm×6 cm.
[0113] No benzene and CO2 were detected at the outlet of the Class III unit, and the magnesium conversion was 65%.
[0114] Example 2
[0115] The adsorption-catalytic degradation material of the I-stage adsorption-catalytic reaction device is Cu-TiO2 / MIL-101(Cr);
[0116] The CO2 capture agent of the Level II CO2 capture device is amine-functionalized Mg-MOF-74.
[0117] 1. Level I adsorption-catalytic reaction device
[0118] (1) Preparation of adsorption-catalytic degradation materials
[0119] The catalytic degradation material comprises 95.5wt% of a catalyst carrier and 4.5wt% of an active component, and the preparation method is as follows:
[0120] a) mixing tetrabutyl titanate with benzyl alcohol, ethanol and water (mass ratio of the four is 4:6:50:1), stirring the mixture at 0°C for 1 hour to mix uniformly, and obtaining a TiO2 sol;
[0121] b) adding Cu(NO3)2·3H2O to the TiO2 sol and stirring for 1 h to obtain a precipitated mixed solution;
[0122] c) centrifuging the precipitated mixture at 500 rpm for 5 min, filtering, and air-drying the resulting solid at room temperature for 24 h;
[0123] d) calcining the air-dried sample at 350°C for 1 h to obtain 4 wt% Cu-TiO2;
[0124] e) MIL-101(Cr), 4wt% Cu-TiO2 and isopropanol were ultrasonically mixed (the weight ratio of the three was 1:1:65), and the mixed sample was ultrasonically dispersed for 30 minutes, and then magnetically stirred for 8 hours to obtain a reaction sample;
[0125] f) The reaction sample was centrifuged and filtered in sequence, and the filtered solid was washed three times with isopropanol and allowed to air-dry at room temperature for 48 hours;
[0126] g) The air-dried sample was mixed with ultrapure water at a weight ratio of 1:50 and transferred to a 150°C autoclave for 10 h, cooled to room temperature, filtered and dried at 110°C for 25 h to obtain 4 wt% Cu-TiO2 / MIL-101(Cr).
[0127] (2) Reaction conditions
[0128] In the photocatalytic oxidation degradation reaction, the relative humidity of the benzene-containing waste gas to be reacted is 40%, and the reaction space velocity is 150h -1 , the visible light source is a 20W lamp, and the visible light power density is 0.1W·cm 2 , the irradiation time was 36 h; the reaction was carried out at room temperature.
[0129] 2. Level II CO2 capture device
[0130] (1) Preparation of amine-functionalized Mg-MOF-74
[0131] a) mixing 4,4′-dihydroxy-3,3′-biphenyldicarboxylic acid, magnesium nitrate, ethanol and DMF in a flask (the mass ratio of the four reagents is 1:3:0.5:0.5) and dispersing to form an emulsion;
[0132] b) sealing the flask and heating and stirring at 120° C. for 24 h to obtain a mixture containing a precipitate;
[0133] After filtering the mixture, the obtained solid was washed three times with fresh DMF reagent, then soaked in methanol three times, and filtered to obtain a solid sample;
[0134] c) heating the solid sample at 200° C. to remove the solvent in the sample to obtain Mg-MOF-74;
[0135] d) Under N2 atmosphere, Mg-MOF-74, diethylenetriamine and hexane were mixed evenly in a flask (the mass ratio of the three was 100:1:10), sealed and allowed to stand for 4 hours to obtain an aminated sample;
[0136] e) The aminated sample was washed three times with hexane and heated at 100° C. under vacuum to remove the solvent in the pores for 4 h to obtain aminated Mg-MOF-74, i.e., a CO2 capture agent.
[0137] (2) Reaction conditions
[0138] The outer wall heater of the II-stage CO2 capturer is controlled to make the desorption temperature 130°C, the desorption time of the CO2 capture agent 8h, the adsorption amount of CO2 by the CO2 capture agent 320mg / g, and the adsorption is carried out at room temperature.
[0139] 3. Class III CO2 application device
[0140] CO2 mineralization is combined with solvent extraction so that the enriched CO2 can continuously convert the Mg in the brine into precipitated MgCO3, so as to achieve effective utilization of tail gas CO2. The solvent used is pentanediol, the extractant is N, N-dioctyl-1-octylamine, and the volume ratio of brine, extractant and solvent is 1.2:1:1;
[0141] In addition, the benzene-containing exhaust gas at the air inlet was controlled to be 100 mL / min, the loading amount of the adsorption-catalytic degradation material was 35 mL, and the size of the catalytic reactor was 4 cm×5 cm×6 cm.
[0142] No benzene and CO2 were detected at the outlet of the Class III unit, and the magnesium conversion was 70%.
[0143] Example 3
[0144] The benzene-containing waste gas was treated according to the method of Example 1, except that the reaction conditions in the first-stage adsorption-catalytic reaction device were adjusted, specifically controlling:
[0145] The relative humidity of the benzene-containing waste gas to be reacted is 20%, and the reaction space velocity of adsorption-catalytic degradation is 150h -1 The visible light source is a 20W lamp tube, and the visible light power density is 0.05W·cm 2 , the irradiation time is 24h.
[0146] The flow rate of benzene-containing exhaust gas at the air inlet was controlled to be 100 mL / min, the loading amount of the adsorption-catalytic degradation material was 35 mL, and the size of the catalytic reactor was 4 cm×5 cm×6 cm.
[0147] The final exhaust gas detected at the outlet of the Class III device is 2 mg·m -3 Benzene, no CO2 detected, magnesium conversion rate was 52%.
[0148] Example 4
[0149] The benzene-containing waste gas was treated according to the method of Example 1, except that the reaction conditions in the first-stage adsorption-catalytic reaction device were adjusted, specifically controlling:
[0150] The relative humidity of the benzene-containing waste gas to be reacted is 60%, and the reaction space velocity of adsorption-catalytic degradation is 150h -1 The visible light source is a 20W lamp tube, and the visible light power density is 0.05W·cm2 , the irradiation time is 24h.
[0151] The flow rate of benzene-containing exhaust gas at the air inlet was controlled to be 100 mL / min, the loading amount of the adsorption-catalytic degradation material was 35 mL, and the size of the catalytic reactor was 4 cm×5 cm×6 cm.
[0152] The final exhaust gas detected at the outlet of the III-stage reaction device was 6 mg·m -3 Benzene, no CO2 detected, magnesium conversion rate was 48%.
[0153] Example 5
[0154] The benzene-containing waste gas was treated according to the method of Example 2, except that the Mg-MOF-74 prepared in Example 2 was used as the CO2 capture agent, and the CO2 adsorption capacity was 88 mg / g. The final exhaust gas detected at the outlet of the Class III device was 5 mg·m -3 CO2, no benzene was detected, and the magnesium conversion rate was 42%.
[0155] Example 6
[0156] The adsorption-catalytic degradation material of the I-stage adsorption-catalytic reaction device is Cu-TiO2 / MIL-101(Cr);
[0157] The CO2 capture agent of the Level II CO2 capture device is amine-functionalized Mg-MOF-74.
[0158] 1. Level I adsorption-catalytic reaction device
[0159] (1) Preparation of adsorption-catalytic degradation materials
[0160] The catalytic degradation material comprises 98.5wt% of a catalyst carrier and 1.5wt% of an active component, and the preparation method is as follows:
[0161] a) mixing tetrabutyl titanate with benzyl alcohol, ethanol and water (mass ratio of the four is 4:6:50:1), and stirring the resulting mixture at 0° C. for 1 h to mix uniformly to obtain a TiO2 sol;
[0162] b) adding Cu(NO3)2·3H2O to the TiO2 sol and stirring for 1 h to obtain a precipitated mixed solution;
[0163] c) centrifuging the precipitated mixture at 500 rpm for 5 min, filtering, and air-drying the resulting solid at room temperature for 36 h;
[0164] d) calcining the air-dried sample at 400°C for 1 h to obtain 6 wt% Cu-TiO2;
[0165] e) MIL-101(Cr), 6wt% Cu-TiO2 and isopropanol were ultrasonically mixed (the weight ratio of the three was 1:1:65), and the mixed sample was ultrasonically dispersed for 30 minutes, and then magnetically stirred for 8 hours to obtain a reaction sample;
[0166] f) The reaction sample was centrifuged and filtered in sequence, and the obtained solid was washed three times with isopropanol and air-dried at room temperature for 48 hours;
[0167] g) The air-dried sample was mixed with ultrapure water at a weight ratio of 1:50 and transferred to a 150°C autoclave for 11 hours, cooled to room temperature, filtered and dried at 120°C for 24 hours to obtain 6 wt% Cu-TiO2 / MIL-101(Cr).
[0168] (2) Reaction conditions
[0169] In the photocatalytic oxidation degradation reaction, the relative humidity of the benzene-containing waste gas to be reacted is 40%, and the reaction space velocity is 150h -1 The visible light source is a 20W lamp tube, and the visible light power density is 0.05W·cm 2 , the irradiation time is 48h; the reaction is carried out at room temperature.
[0170] 2. Level II CO2 capture device
[0171] (1) Preparation of amine-functionalized Mg-MOF-74
[0172] a) mixing 4,4′-dihydroxy-3,3′-biphenyldicarboxylic acid, magnesium nitrate, ethanol and DMF in a flask (the mass ratio of the four reagents is 1:3:0.5:0.5) and dispersing to form an emulsion;
[0173] b) sealing the flask and heating and stirring at 120° C. for 24 h to obtain a mixture containing a precipitate;
[0174] After filtering the mixture, the obtained solid was washed three times with fresh DMF reagent, then soaked in methanol three times, and filtered to obtain a solid sample;
[0175] c) heating the solid sample at 200° C. to remove the solvent in the sample to obtain Mg-MOF-74;
[0176] d) Under N2 atmosphere, Mg-MOF-74, tetraethylenepentamine and hexane were mixed evenly in a flask (the mass ratio of the three was 100:1:10), sealed and allowed to stand for 4 hours to obtain an aminated sample;
[0177] e) The aminated sample was washed three times with hexane and heated and evacuated at 100° C. to remove the solvent in the pores for 4 h to obtain an aminated Mg-MOF-74 sample, i.e., a CO2 capture agent.
[0178] (2) Reaction conditions
[0179] The heater on the outer wall of the II-stage CO2 capturer is controlled to make the desorption temperature 120°C, the desorption time of the CO2 capture agent 8h, the adsorption amount of CO2 by the CO2 capture agent 280mg / g, and the adsorption is carried out at room temperature.
[0180] 3. Class III CO2 application device
[0181] CO2 mineralization is combined with solvent extraction so that the enriched CO2 can continuously convert the Mg in the brine into precipitated MgCO3, so as to achieve effective utilization of tail gas CO2. The solvent is isoamyl alcohol, the extractant is triethylamine, and the volume ratio of brine, extractant and solvent is 1.2:1:1;
[0182] In addition, the benzene-containing waste gas at the air inlet was controlled to be 100 mL / min, the loading amount of the adsorption-catalytic degradation material was 35 mL, and the size of the catalytic reactor was 4 cm×5 cm×6 cm.
[0183] No benzene and CO2 were detected at the outlet of the Class III unit, and the magnesium conversion was 54%.
[0184] In the above Examples 1-4 and 6, the VOC degradation efficiency and CO2 application results of different materials are shown in Table 1.
[0185] Table 1
[0186]
[0187] 1: indicates the CO2 concentration in the outlet gas of the Class III device, 2: indicates the benzene concentration in the outlet gas of the Class III device. / indicates that the detected object is below the instrument detection limit.
[0188] Example 7
[0189] The benzene-containing waste gas was treated according to the method of Example 1, except that when preparing the catalytic degradation material, MIL-101(Cr) was replaced by HKUST-1 of equal mass (prepared according to the literature, DOI: 10.1021 / ja056639q). The relative humidity of the gas to be reacted was controlled to be 50%; the final exhaust gas detected at the outlet of the Class III device was 3 mg·m- 3 Benzene, no CO2 detected, magnesium conversion rate was 55%.
[0190] Example 8
[0191] The benzene-containing waste gas was treated according to the method of Example 1, except that when preparing the catalytic degradation material, MIL-101(Cr) was replaced by UIO66 of equal mass (prepared according to the literature, DOI: 10.1016 / j.apsusc.2014.11.103). The relative humidity of the gas to be reacted was controlled to be 50%; the final exhaust gas discharged at the exhaust outlet of the Class III device was detected to be 5 mg·m -3 Benzene, no CO2 detected, magnesium conversion rate was 43%.
[0192] Example 9
[0193] The benzene-containing waste gas was treated according to the method of Example 1, except that when preparing the CO2 capture agent, it was replaced with an equal mass of ZIF-8 (prepared according to the literature, DOI: 10.1073 / pnas.0602439103). The relative humidity of the gas to be reacted was controlled to be 50%; the final exhaust gas detected at the outlet of the Class III device was 6 mg·m -3 CO2, no benzene was detected, and the magnesium conversion rate was 42%.
[0194] Example 10
[0195] The benzene-containing waste gas was treated according to the method of Example 1, except that when preparing the CO2 capture agent, it was replaced with an equal mass of MIL-53 (Al) (prepared according to the literature, DOI: 10.1002 / chem.200305413). The final exhaust gas detected at the outlet of the Class III device was 8 mg·m -3 CO2, no benzene was detected, and the magnesium conversion rate was 35%.
[0196] As can be seen from the above, the present invention aims at the problems of low VOC degradation efficiency, poor CO2 capture effect, and non-integration of VOC and CO2. By introducing microporous materials as catalyst carriers, the adsorption and degradation efficiency of VOC by the catalyst composite material is improved; by introducing amine-functionalized MOF materials, the capture effect of the adsorption material on CO2 is greatly enhanced; by further desorbing and concentrating the captured CO2 and using it in the high magnesium-lithium ratio brine treatment industry, the tail gas CO2 is eliminated through mineralization, thereby achieving one-time degradation of VOC and efficient utilization of tail gas CO2.
[0197] In addition, the comparative results of Example 1 and Examples 3-4 show that humidity has an effect on the VOC degradation efficiency. Since water can react with the holes generated on the catalyst surface to form hydroxyl radicals to promote the catalytic oxidation process of VOC, the presence of an appropriate amount of water is conducive to the photocatalytic reaction. However, too low humidity or too high humidity will have an adverse effect on the photocatalytic reaction. Under 20% humidity conditions, lower water content leads to the production of fewer hydroxyl radicals, thereby affecting the VOC degradation efficiency of the catalyst in the system. On the contrary, under 60% humidity conditions, a large amount of water and VOC form competitive adsorption on the surface of the catalyst composite material, especially water tends to preferentially occupy the active sites on the surface of the material, resulting in the catalytic reaction mainly occurring at the interface between the catalyst surface and the free VOC gas, thereby reducing the VOC degradation efficiency.
[0198] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
[0199] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
Claims
1. A method for treating VOC waste gas, characterized in that: The method includes: 1) In the presence of adsorption-catalytic degradation materials, VOC waste gas is subjected to photocatalytic degradation reaction to obtain degradation products containing CO2 and water; 2) in the presence of a CO2 capture agent, capturing CO2 in the degradation product, allowing CO2 to be adsorbed on the CO2 capture agent, and then desorbing and concentrating to obtain enriched CO2, wherein the CO2 capture agent is a MOF adsorption material II or an organic amine-modified MOF adsorption material II, the MOF adsorption material II is selected from at least one of Mg-MOF-74, ZIF-8 and MIL-53 (Al), and the organic amine is selected from at least one of ethylenediamine, diethylenetriamine and tetraethylenepentamine; Wherein, the organic amine-modified MOF adsorption material II is prepared by a method comprising the following steps: Step I: Under an inert atmosphere, MOF adsorbent material II, organic amine and hexane are mixed evenly in a mass ratio of (98-101) : 1 : (9-11), and then allowed to stand for 3-6 hours to obtain an aminated sample; Step II: washing the aminated sample with hexane and drying; 3) mixing the enriched CO2 with salt lake brine with a high magnesium-lithium ratio to mineralize the magnesium in the brine with CO2; In step 1), the adsorption-catalytic degradation material comprises a catalyst carrier and an active component; the catalyst carrier is a MOF adsorption material I, and the active component comprises TiO2 and a doping metal, wherein the MOF adsorption material I is MIL-101 (Cr), the doping metal is copper and / or cerium, and the content of the doping metal in terms of its oxide is 1-6 wt % based on the total weight of the active component; Based on the total weight of the adsorption-catalytic degradation material, the content of the catalyst carrier is 92-99% by weight, and the content of the active component is 1-8% by weight; The adsorption-catalytic degradation material is prepared by a method comprising the following steps: A) mixing tetrabutyl titanate, benzyl alcohol, ethanol and water in a mass ratio of (3-5):(5-7):(48-51):1 and stirring the mixture at 0-5° C. to obtain a TiO2 sol; B) adding a soluble salt of a doped metal to the TiO2 sol, stirring, and obtaining a precipitation mixed solution; C) centrifuging and filtering the precipitated mixed solution, and air-drying the solid obtained by filtration; D) calcining the air-dried sample to obtain the active component; E) mixing the MOF adsorbent material I, the active component and isopropanol, and performing ultrasonic dispersion to obtain a dispersion; F) subjecting the dispersion to magnetic stirring, centrifugation, and filtering, and washing the solid obtained after filtering with isopropanol and standing to air-dry; G) The air-dried sample is mixed with water and transferred to an autoclave and kept at 130-150° C. for 8-12 hours, then cooled and filtered to obtain the adsorption-catalytic degradation material.
2. The processing method according to claim 1, characterized in that: The VOC in the VOC waste gas is at least one of benzene, toluene, ethylbenzene, xylene, chlorobenzene, styrene, formaldehyde and acetaldehyde; The VOC concentration in the VOC waste gas is lower than 150 mg·m -3 .
3. The processing method according to claim 1, characterized in that: The VOC in the VOC waste gas is at least one of benzene, toluene, ethylbenzene and xylene; the VOC concentration in the VOC waste gas is lower than 120 mg·m -3 .
4. The processing method according to claim 1, characterized in that: In step 1), the reaction conditions of the photocatalytic degradation reaction include: a reaction space velocity of 150-200h -1 , the visible light is provided by a lamp with a power of 20-30W, and the power density of the visible light is 0.05-0.1W / cm 2 , the lamp irradiation time is 24-48h; This step controls the relative humidity of the VOC waste gas to 20-60%.
5. The processing method according to claim 4, characterized in that: Control the relative humidity of VOC exhaust gas to 30-50%.
6. The processing method according to claim 1, characterized in that: The CO2 capture agent is Mg-MOF-74 modified with organic amine.
7. The processing method according to claim 1, characterized in that: In step 2), the CO2 capture agent has an adsorption capacity of 88-350 mg / g for CO2, a desorption temperature of 100-135° C., and a desorption time of 8-10 h.
8. The processing method according to claim 1, characterized in that: Step 3) includes: 3-1) In the presence of an extractant and a solvent, the enriched CO2 and the high magnesium-lithium ratio salt lake brine are mixed and stirred for reaction; wherein the extractant is selected from N,N-dioctyl-1-octylamine and / or triethylamine, and the solvent is selected from at least one of butanediol, pentanediol and isopentanol; during the stirring reaction, MgCO3 precipitate and HCl are generated, and HCl reacts with the extractant to form an ammonium salt; 3-2) The solid-liquid product containing MgCO3 and ammonium salt obtained in step 3-1) is filtered to obtain a filter cake and a filtrate. The filter cake is washed and dried to obtain MgCO3. The filtrate is allowed to stand and separated to obtain an aqueous phase containing lithium brine.
9. The processing method according to claim 8, characterized in that: The volume ratio of the high magnesium-lithium ratio salt lake brine, the extractant and the solvent is (1-1.2): (0.8-1.2): 1, and the stirring reaction time is 2-2.5 hours.
10. The processing method according to claim 8, characterized in that: The mass ratio of MgCl2 to LiCl in the high magnesium-to-lithium ratio salt lake brine is (25-30) to 1 in terms of Mg / Li.
11. The VOC waste gas treatment device used in the treatment method according to any one of claims 1 to 10, characterized in that: The treatment device comprises a first-level adsorption-catalytic reaction device, a second-level CO2 capture device (8) and a third-level CO2 application device (13) which are connected in sequence, wherein: The first-stage adsorption-catalytic reaction device is used to enrich the VOC waste gas and photocatalytically degrade it into degradation products containing CO2 and H2O; The stage II CO2 capture device (8) is used to capture, desorb and concentrate the CO2 in the degradation product to obtain enriched CO2; The III-level CO2 application device (13) is used to contact the enriched CO2 with high magnesium-lithium ratio salt lake brine to mineralize magnesium.
12. The processing device according to claim 11, characterized in that The first-level adsorption-catalytic device is provided with a VOC waste gas inlet (1), a primary dust removal component (2), an intermediate dehumidification component (3), and a closed light-shielding reaction chamber (4); wherein the top of the closed light-shielding reaction chamber (4) is provided with light-transmitting quartz and a top lamp (5a), the bottom is provided with light-transmitting quartz and a bottom lamp (7a), and the middle is a catalytic reactor (6) filled with the adsorption-catalytic degradation material; the primary dust removal component (2) is used to filter dust in the VOC waste gas, and the intermediate dehumidification component (3) is used to remove moisture in the VOC waste gas; The interior of the II-stage CO2 capture device (8) is provided with a dehumidification component (9), a CO2 adsorption component (10) and a CO2 desorption fan (11) from top to bottom, wherein the CO2 adsorption component (10) contains the CO2 capture agent and is provided with a heater on the outside thereof, and the heater is used to provide a desorption temperature for desorbing CO2; The III-level CO2 application device (13) is provided with an exhaust gas outlet (16) after purification and a lithium purification component from brine with a high magnesium-lithium ratio. The component is provided with a reactor (14), a filter (17) and a liquid separation device (18) in sequence according to the material flow direction. The reactor (14) is provided with a stirrer (15).
Citation Information
Patent Citations
On-board recovery and storage of CO2 from motor vehicle exhaust gases
CN103403142A
Adsorption-photocatalysis bifunctional material and preparation method thereof, and application of adsorption-photocatalysis bifunctional material in volatile organic gas treatment process
CN106861626A